2015
DOI: 10.3390/ijms160818732
|View full text |Cite
|
Sign up to set email alerts
|

LincRNA-p21: Implications in Human Diseases

Abstract: Long noncoding RNAs (lncRNAs), which lack significant protein-coding capacity, regulate various biological processes through diverse and as yet poorly understood molecular mechanisms. However, a number of studies in the past few years have documented important functions for lncRNAs in human diseases. Among these lncRNAs, lincRNA-p21 has been proposed to be a novel regulator of cell proliferation, apoptosis and DNA damage response, and involved in the initiation and progression of human diseases. In this review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 36 publications
2
45
0
Order By: Relevance
“…Since its discovery in 2010, Linc-p21 has been the subject of intense study due to its reported roles in important biological processes (Huarte et al, 2010, Dimitrova et al, 2014, Yang et al, 2014, Hall et al, 2015, Bao et al, 2015, Yoon et al, 2012, Wu et al, 2014, Wang et al, 2014, Tran et al, 2015, Tang et al, 2015). However, despite extensive investigation, the nature of transcription at the Linc-p21 locus and the mechanism by which the gene functions have not been tested outside of cell-based assays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its discovery in 2010, Linc-p21 has been the subject of intense study due to its reported roles in important biological processes (Huarte et al, 2010, Dimitrova et al, 2014, Yang et al, 2014, Hall et al, 2015, Bao et al, 2015, Yoon et al, 2012, Wu et al, 2014, Wang et al, 2014, Tran et al, 2015, Tang et al, 2015). However, despite extensive investigation, the nature of transcription at the Linc-p21 locus and the mechanism by which the gene functions have not been tested outside of cell-based assays.…”
Section: Discussionmentioning
confidence: 99%
“…Linc-p21 is one of the most-studied lncRNAs due to its role in p53 signalling and relevance to human disease (Huarte et al, 2010, Dimitrova et al, 2014, Yoon et al, 2012, Tang et al, 2015). Indeed, since its discovery in 2010, dozens of studies have examined Linc-p21 in human and/or mouse cell-based assays, and have collectively identified roles in a range of biological processes including cell cycle control, reprogramming, apoptosis, and energy metabolism (Dimitrova et al, 2014, Bao et al, 2015, Huarte et al, 2010, Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence suggests that lincRNA-p21, about 3.0 kb in length and located nearly 15 kb upstream of p21/Cdkn1a gene, is a new regulator of cell cycle, apoptosis and DNA repair, and plays a vital role in some diseases including cancer [1417]. As a p53-induced lincRNA, lincRNA-p21 employs the heterogeneous nuclear ribonucleoprotein K (hnRNP-K) protein to oppress transcription of p53 target gene [18].…”
Section: Introductionmentioning
confidence: 99%
“…The LINCRNA‐P21 has a key role in regulating P21 levels, a CDK2 inhibitor. In hepatocellular carcinoma, down‐regulation of LINCRNA‐P21 was observed and, when its expression was induced, cell proliferation and colony formation were inhibited …”
Section: Lncrnas In Hallmarks Of Cancermentioning
confidence: 99%